Komunikasi Interpersonal di Dinas Perindustrian dan Perdagangan Provinsi Sumatera Barat - Yuniati, Yuniati; Ermita, Ermita (YASIN, 2025)
The purpose of this research is to find out and obtain information about employee interpersonal communication as seen from: (1) openness, (2) empathy, (3) support, (4) positive feelings and (5) equality in the Sumatra Province Industry and Trade Service West. The research questions are: how good is (1) openness, (2) empathy, (3) support, (4) positive feelings, and (5) equality in the West Sumatra Province Department of Industry and Trade. This type of research is descriptive quantitative with the population being all employees at the Department of Industry and Trade of West Sumatra Province, totaling 61 people. The instrument used was a questionnaire with a Likert scale model with five answer choices, namely always (SL), often (SR), sometimes (KD), rarely (JR), never (TP). Before the questionnaire was used, it was tested on 30 employees at the West Sumatra Province Transportation Service and processed using the SPSS version 27 program, the results were declared valid and reliable. Data is processed using the mean formula (average score). The results of processing the research data obtained can be seen from: (1) openness has been implemented well with an average score of 3.81, (2) Empathy has been implemented well with an average score of 3.82, (3) Support has been implemented well with an average score of 3.90, (4) Positive Feeling has been implemented well with an average score of 3.77 and (5) equality has been implemented well with an average score of 3.82. From the research results above, it can be concluded that interpersonal communication at the West Sumatra Province Department of Industry and Trade has been implemented well with an average score of 3.82.